Evaluation of Traffic Light Effectiveness on The Toll Overpass Segment on The Sidodadi Road, Candi District, Sidoarjo Regency - Helmi Riezki Latif; Risma Marleno; Haris Muhammadun (Journal of Social Science, 2025)
The evaluation of traffic light effectiveness is critical for optimizing road performance and minimizing congestion, particularly in high-traffic areas such as the overpass segment of Sidodadi Road, Candi District, Sidoarjo Regency. This study analyzes the performance of traffic lights in regulating vehicle flow at intersections and proposes improvements to enhance traffic efficiency and safety. Using the Indonesian Highway Capacity Manual (MKJI) 1997 as the analytical framework, this research examines traffic volume, degree of saturation, delays, and service levels under current traffic light configurations. Data were collected through traffic volume surveys during peak hours and included vehicle composition, intersection geometry, and traffic light cycle timing. The analysis revealed significant congestion during morning and evening peak hours, with a degree of saturation exceeding the recommended threshold. The delays and service levels indicated suboptimal performance, necessitating adjustments to traffic light timing and phase configurations. The study proposes two key alternatives to address these issues: short-term adjustments to traffic light cycles to accommodate peak-hour traffic and long-term solutions involving the redesign of intersection geometry and the implementation of adaptive traffic control systems. These recommendations aim to balance traffic flow, reduce delays, and prevent potential deadlock scenarios. This research underscores the importance of periodic evaluations and the integration of advanced technologies such as real-time adaptive traffic systems to optimize road performance and support regional economic activities. The findings contribute valuable insights for policymakers and stakeholders in improving traffic management strategies in similar urban settings